2015
DOI: 10.12707/riv15014
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of the Escala de Comportamentos de Abordagem aos Média por Enfermeiros (Scale of Media Use Behaviours by Nurses)

Abstract: As mensagens mediáticas sobre a saúde em Portugal tendem a desvalorizar o contributo dos enfermeiros e podem originar representações redutoras do setor. Compreender como os enfermeiros abordam os média torna-se fundamental para caracterizar esta problemática. Objetivos: Construir e validar a Escala de Comportamentos de Abordagem aos Média por Enfermeiros. Metodologia: Realizou-se um estudo metodológico numa amostra de enfermeiros pertencentes à mesma rede social (n=528). O processo de validação incluiu a análi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The paradox experienced by the participants coincides with a study that identified a low frequency of interaction between nurses and the media (average of 6.24 points on a scale of 92 points) (20) . Some PNA leaders are suspicious of the media and their methods and recognize that they could play a more active role in this interaction.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The paradox experienced by the participants coincides with a study that identified a low frequency of interaction between nurses and the media (average of 6.24 points on a scale of 92 points) (20) . Some PNA leaders are suspicious of the media and their methods and recognize that they could play a more active role in this interaction.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to media attention, it is intended to increase the importance of the association in the eyes of journalists and the public (standing) and obtain a favorable framing (preferred framing) of messages to be communicated (12) . Research produced in recent years have revealed: the scarce media coverage of the profession, with nurses being news sources in 1.5% to 6.6% of the total published health related news (7,(16)(17)(18) ; the media discourse tending to be negative, focusing on work problems, the shortage of nurses, and scandals in the profession (5,11,16,19) ; the reduced frequency of nurses' interaction with mass media (20) ; the existence of limited resources (reduced number of members and funding), the lack of formal communication structures, such as communication offices or spokespersons trained to interact with the media; and the spread of a discourse centered on professionals and little directed at citizens (21) .…”
Section: Introductionmentioning
confidence: 99%
“…Nurses tend to communicate the profession's views by exposing their problems (such as nursing shortage and safe staffing), which prevents the public from understanding what they know and do as nurses . Graveto et al explored the frequency of nurses' interaction with the media by building and validating the Scale of Media Use Behaviors by Nurses in a sample of 528 Portuguese nurses. This 23‐item Likert‐type scale describes ways of interacting with the media (such as writing press releases or inviting the media for professional nursing events).…”
Section: Introductionmentioning
confidence: 99%